2008
DOI: 10.1177/135965350801300810
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C as a Marker of Renal Function is Affected by HIV Replication Leading to an Underestimation of Kidney Function in HIV Patients

Abstract: Background Broad use of tenofovir and an ageing HIV-infected population have created an interest in renal function in HIV patients. Serum cystatin C is a newer marker of renal function and might be more sensitive than creatinine. Methods Patients were enrolled consecutively in an observational study. HIV-seropositive patients naive to antiretroviral therapy ( n=261) were compared with healthy volunteers undergoing check-up procedures ( n=193). Estimated glomerular filtration rate (eGFR) was derived using creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 21 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…inflammatory markers in the general population [19,20], and has been reported to be correlated with HIV RNA levels, hepatitis C coinfection, and T-cell activation indices in HIV-infected persons [21][22][23]. In both the general population and in HIVinfected persons, cystatin C is a stronger predictor of mortality and cardiovascular events than creatinine or creatinine-based GFR estimates [24][25][26][27].…”
Section: Kidney Function and Damage Markersmentioning
confidence: 99%
“…inflammatory markers in the general population [19,20], and has been reported to be correlated with HIV RNA levels, hepatitis C coinfection, and T-cell activation indices in HIV-infected persons [21][22][23]. In both the general population and in HIVinfected persons, cystatin C is a stronger predictor of mortality and cardiovascular events than creatinine or creatinine-based GFR estimates [24][25][26][27].…”
Section: Kidney Function and Damage Markersmentioning
confidence: 99%
“…The present study focused on PWH treated with antiretroviral drugs aged around 60 (AE10.7) years without significant difference between groups for age and BMI, which could have impacted creatinine levels [32] and with suppressed HIV viral load to avoid impact on cystatin C [29]. As a current hypothesis, overestimation of plasma creatinine because of ICS exposure would erroneously decrease the eGFR.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, increased levels are encountered in the general population in hyperthyroidism or under glucocorticoids use [27,28]. In PWH, increased levels had been reported in cases of uncontrolled viral load [29]. Otherwise, decreased levels occur notably in hypothyroidism and in several cancers [27,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that Cys C plays a crucial role in regulating antigen presentation, protecting the host from microbial invasion, and inhibiting viral replication and growth [ 20 23 ]. Elevated Cys C levels associated with high viral loads have been found in HIV patients [ 24 ]. We boldly hypothesized that elevated serum Cys C might be a function of the immune defense against the high load of Mtb in cavitary PTB.…”
Section: Discussionmentioning
confidence: 99%